THE DEVELOPMENT GEMATIKA AS A WEBSITE-BASED MATHEMATICS LEARNING MEDIA ON COMPARISON MATERIALS - Firdayana Makmur; Sri Andayani; Vevi Arini Azizatus Sufaidah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
Technology-based learning media in the learning process must be applied in today's digital era. GEMATIKA as website-based mathematics learning media was developed to support students' mathematics learning, especially Comparative material. This study aims to determine the process of developing learning media based on the GEMATIKA website that meets valid and practical criteria. This type of research is development research using the ADDIE development model. Data was collected using material and media expert validation sheets and student response questionnaires to the GEMATIKA website learning media. The subjects of this study consisted of 28 students from class VII. The results showed that the results of media validation by material experts and media experts were 4.13 and 4.29. The average percentage of student response questionnaire results is 80.82%. It means that students respond positively after using the GEMATIKA learning media. The positive responses indicate that students support, feel happy, and are interested in using the GEMATIKA website learning media in the mathematics learning process at home or in class. Based on the results of the validation sheet and student response questionnaires, it can be concluded that the GEMATIKA website learning media meets the valid and practical criteria